The C(1)-C(α) torsional potential function of 2-fluorostyrene from S1-S0 fluorescence in a supersonic jet - Hollas, J. Michael; Hussein, Mohd Zobir (Elsevier, 1989)
Single vibronic level fluorescence spectra of tram-2-fluorostyrene have been observed in a supersonic jet. Levels of the C(1)-C(a)torsional vibration up to u=8 are fitted to a potential function which shows that the molecule is quasi-planar with a barrier of I5+4 cm-’.